Attuning: A Communication Process between People with Severe and Profound Intellectual Disability and Their Interaction Partners. Issue 2 (5th March 2015) - Griffiths, Colin; Smith, Martine
Abstract : Background: People with severe and profound intellectual disability typically demonstrate a limited ability to communicate effectively. Most of their communications are non‐verbal, often idiosyncratic and ambiguous. This article aims to identify the process that regulates communications of this group of people with others and to describe the methodological approach that was used to achieve this. Materials and Methods: In this qualitative study, two dyads consisting of a person with severe or profound intellectual and multiple disability and a teacher or carer were filmed as they engaged in school‐based activities. Two 1‐hour videotapes were transcribed and analysed using grounded theory. Results: Attuning was identified within the theory proposed here as a central process that calibrates and regulates communication. Conclusion: Attuning is conceptualized as a bidirectional, dyadic communication process. Understanding this process may support more effective communication between people with severe or profound intellectual and multiple disability and their interaction partners.